1966
DOI: 10.1080/00288233.1966.10420772
|View full text |Cite
|
Sign up to set email alerts
|

Changes in forms of soil inorganic phosphorus in Lismore stony silt loam due to application of superphosphate to pasture

Abstract: Changes in available phosphorus (as extracted by the Truog and Olsen methods) and in phosphorus held in the soil in aluminium-, iron-, and calcium-bound forms have been followed on soil samples taken from a rates of superphosphate trial on irrigated pasture from 1952 to 1964.Truog phosphorus levels in samples taken at three-monthly intervals showed a cyclic pattern due to the annual fertiliser applications, the fluctuations being greater at higher rates of superphosphate.In samples taken just before top-dressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1972
1972
1981
1981

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Similar to the findings of Grigg 11 Evidently, as fixation became more complete in the "FePOj," The lack of a significant yield response to superphosphate lu additions indicated that the relatively low soil P levels in the control plots were adequate for the strawberry cv.…”
Section: Introductionsupporting
confidence: 76%
“…Similar to the findings of Grigg 11 Evidently, as fixation became more complete in the "FePOj," The lack of a significant yield response to superphosphate lu additions indicated that the relatively low soil P levels in the control plots were adequate for the strawberry cv.…”
Section: Introductionsupporting
confidence: 76%
“…Mean ir.organic phosphorus concentrations in the 1971 samples from irrigated and control sites were slightly less than the mean concentrations of the 1945 samples. Grigg (1966) reported a decrease with time in the aluminium-bound phosphorus content of irrigated Lismore stony silt loam at a fertiliser rate of 190 kg superphosphate/ha/yr, but not at higher rates of superphosphate application. As the mean superphosphate application on the sites being discussed was 190 kg/yr, it is suggested that the decreases in inorganic phosphorus found in the 1971 samples could reflect the same effect as that reported by Grigg.…”
Section: Phosphorusmentioning
confidence: 96%